Redefining disease in the age of blood-based biomarkers - Reddy, Naveen K. (Frontiers in Sociology, 2025)
This article explores the sociological and ethical implications of redefining disease in the era of advanced diagnostic technologies, with a focus on blood-based biomarkers. Drawing from Foucault's concept of medicalization and Illich's critique of disease mongering, it highlights how diagnostic expansions, driven by corporate and institutional influences, are reshaping the boundaries of health and disease. Advances such as blood assays for Alzheimer's and Parkinson's diseases, liquid biopsies in oncology, and biomarkers for depression and diabetes, while promising, raise concerns about premature diagnoses and overtreatment. The influence of pharmaceutical and insurance industries on diagnostic criteria, as seen in the ICD updates, underscores the need to address conflicts of interest and regulatory gaps. Case studies on Alzheimer's and Parkinson's reveal how these changes could benefit stakeholders at the expense of patient welfare. The article calls for ethical oversight, stricter regulation, and research into the population-level efficacy of diagnostic and treatment protocols.